Las tic: nuevos lenguajes, nuevas prácticas (Papeles, 2009)
This article has the first topic review on the investigation project The cit as new forms of interaction: a tool for the language students, approved by the Universidad Antonio Nariño. In the first instance, it raises the importance of promoting investigations that aim to a rigorous inquiry on the languages that propose the new technologies, as well as on the relations that the users establish with them to come to a significant reference margin that contributes to the constitution of educational spaces that involve the cit in a relevant way, that is to say, that are in conjunction with the practices that the above mentioned means promote. Secondly, it gives account of the first review of the state of the art of the investigations done on the cit and education. Finally, it does a brief approximation to the proposal as such of the approved project, that consists on the narratives and manners of fiction that they can find in some virtual worlds as those proposed by the Role Playing Games.
Keywords: CIT; education; fiction; practices; languages